Aqueous‐Phase Sampling with NAPL Exclusion Using Ceramic Porous Cups. Issue 6 (25th September 2018) - Gefell, Michael J.; Kanematsu, Masa; Vlassopoulos, Dimitri; Lipson, David S.
Abstract : Article impact statement : We demonstrate aqueous sampling methods using ceramic porous cups to exclude NAPL from water samples, even in direct contact with NAPL.